2015
DOI: 10.1186/s12885-015-1230-0
|View full text |Cite
|
Sign up to set email alerts
|

NPC1L1 knockout protects against colitis-associated tumorigenesis in mice

Abstract: BackgroundColorectal cancer is strongly associated with lipid metabolism. NPC1L1, a sterol transporter, plays a key role in modulating lipid homeostasis in vivo. Its inhibitor, ezetimibe, began to be used clinically to lower cholesterol and this caused the great debate on its role in causing carcinogenesis. Here we explored the role of NPC1L1 in colorectal tumorigenesis.MethodsWild-type mice and NPC1L1−/− (NPC1L1 knockout) mice were treated with azoxymethane (AOM)-dextran sodium sulfate (DSS) to induce colitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 30 publications
1
62
0
Order By: Relevance
“…Studies in mice have shown that knocking out the cell surface cholesterol-sensing receptor gene NPC1L1, which plays a critical role in the absorption of intestinal cholesterol, reduces CRC risk. 31 However, the biological mechanism by which cholesterol may affect CRC risk remains to be established. Cholesterol is thought to have multiple carcinogenic/ cancer promoting effects at the cellular level and several mechanisms have been variously suggested, including the cholesterol-mediated activation of the NLRP3 inflammasome.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in mice have shown that knocking out the cell surface cholesterol-sensing receptor gene NPC1L1, which plays a critical role in the absorption of intestinal cholesterol, reduces CRC risk. 31 However, the biological mechanism by which cholesterol may affect CRC risk remains to be established. Cholesterol is thought to have multiple carcinogenic/ cancer promoting effects at the cellular level and several mechanisms have been variously suggested, including the cholesterol-mediated activation of the NLRP3 inflammasome.…”
Section: Discussionmentioning
confidence: 99%
“…1D). These structures mimicked colorectal tumors at an avascular stage or avascular regions of colorectal tumors in vivo (2,7). The ultrastructure of 3D cultures was observed using a transmission electron microscope.…”
Section: Resultsmentioning
confidence: 98%
“…Colorectal cancer (CRC) is the third most commonly diagnosed cancer in males, and the second most common in females worldwide (1). The highest incidence rates are mainly in developed countries and the incidence is increasing in developing countries, which is partly attributable to lipid metabolism (1)(2)(3). Despite an enormous amount of effort spent in the development of therapies to treat CRC, the 5-year survival rate has increased slowly in the USA, from 60% during the 1980s to 66% during 2005 to 2011 (4).…”
Section: Introductionmentioning
confidence: 99%
“…1 The incidence is increasing in most of developing countries, partly attributing to lipid metabolism. [1][2][3] According to its inci-dence, CRC is categorized in three forms: family, hereditary, and sporadic (about 80% of CRC). 4,5 Many in vitro models and in vivo models have been developed and used in understanding CRC.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…4,5 Many in vitro models and in vivo models have been developed and used in understanding CRC. 2,6 In vivo models include inoculated CRC models and tumors induced by "diet" (high fat, low calcium, etc), by chemical, by gene mutation or genetic modification (APC lines, Kras, Msh2, P53, Rb, and so on). 7-9 Subcutaneous inoculation models are widely used to study responses of CRC to chemotherapy, radiotherapy and other types of therapy 10,11 .…”
Section: Introduction Backgroundmentioning
confidence: 99%